Environmental Disclosure Evaluation Hotels (EDEH). Una propuesta de indicadores y un informe de sustentabilidad basada en el Global Reporting Initiative para empresas hoteleras - Fabricia Silva da Rosa (Estudios y Perspectivas en Turismo, 2012)
The hotel sector is a fundamental activity for worldwide tourism; despite the development of its activities it generates environmental impacts. It is considered, then, the environmental information management as a complex activity that demands performance assessment, and it aims to propose an assessment model and measures of planning and environmental performance control. The aim to be reached was built up EDEH model that proposes a control plan for the environmental indicators and a routine to elaborate sustainability information. The model and processes are applied through a study case in NH Hotels and allows identifying, measuring, managing and controlling the environmental aspects and impacts which are specific of the sector. For further investigations, it is suggested to apply the model in hotels of different sizes, localization and general aspects in order to promote comparisons that allow inferring the influence of these variables about the disclosure environmental performance.